Epoxy putty external skeletal fixation for fractures of the four main metacarpal and metatarsal bones in cats and dogs - Puerta, B. De La; Emmerson, T.; Moores, A. P.; Pead, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
The objective of this retrospective study was to report the clinical use, advantages, disadvantages, complications and outcome of an epoxy putty external skeletal fixator (EPESF) used for the repair of fractures of all four main metatarsal or metacarpal bones in a single limb in 11 dogs and 11 cats. The aim of this technique was to achieve satisfactory alignment of the proximal and distal joints and the digits, rather than anatomical reconstruction of the metacarpal/metatarsal bones themselves. All of the cases achieved fracture union and they all recovered fully without any residual lameness.
Keywords: Fracture; metacarpal; metatarsal; cat; dog